The Role of Digital Capability and Social Media Engagement in Mediating Entrepreneurial Marketing on MSME Marketing Performance in Banyumas Regency - Reza Rahmadi Hasibuan; Sudarto Sudarto (Citakonsultindo, 2024)
This research aims to examine the role of digital capability and social media engagement in mediating the relationship between entrepreneurial marketing and MSME marketing performance in Banyumas Regency. This research uses simple random sampling data analysis techniques with a sample size of 298 respondents from MSMEs in Banyumas Regency. The results of this research are that digital capability has no effect on marketing performance, entrepreneurial marketing has an effect on digital capability, digital entrepreneurial marketing has no effect on marketing performance, entrepreneurial marketing has an effect on social media engagement and social media engagement has an effect on marketing performance.